Models of men: The construction and problematization of masculinities in the Islendingasogur - Evans, G (2015)
This thesis examines masculinities in the Íslendingasögur. It attempts to uncover the dominant model of masculinity that operates in the sagas, outlines how masculinities and masculine characters function within these texts, and investigates the means by which the sagas, and saga characters, may subvert masculine dominance. The thesis applies to men and masculinities in saga literature the same scrutiny traditionally used to study women and femininities. The first – introductory – chapter reviews the limited scholarship that presently exists on masculinities in Old Norse literature. It then proposes a new model for the critical study of saga masculinities, drawing on sociological theories of hegemonic and subordinated masculinities. The second chapter ranges across the entire Íslendingasaga corpus in order to demonstrate how masculinity inflects homosocial relationships (and thus virtually all aspects of saga texts). It also suggests that almost all masculine characters have a problematic relationship with masculinity as a result of the intersectional nature of subject formation. The third chapter, focusing on Njáls saga, argues that the male body is used to undermine the prevailing model of masculinity. It is argued that the Njála author purposefully deploys somatic indices that have gendered significance to show embodied resistance to the demands of masculinity. The fourth chapter examines the representation and treatment of a character (Grettir Ásmundarson) that embodies masculinity to an exceptional degree, but who nevertheless – or perhaps for that reason – experiences a problematic relationship with masculinity. Finally, an epilogue briefly investigates some of the ways in which female characters may undermine and problematize the masculinity of men and the category of masculinity itself. Ultimately, this thesis shows that masculinity is not simply glorified in the sagas, but is represented as being both inherently fragile and a burden to all characters, masculine and non-masculine alike.